Texica Limited (A) : a day in the life of a consultant - Maheshwari, Sunil Kumar; Ray, Prantika (London : Indian Institute of Management, Ahmedabad, 2017)
Texica Limited was a renowned textile company that has been reporting losses for the past few years. The Chairman, Ashutosh Verma decided to seek help from consultants to improve the performance of the company. The consultants found that there was an excess of manpower in the majority of departments and recommended forming a new committee to discuss the hiring of any new employee. Furthermore, the consultants recommended implementing a new safety program known as 6S (Sort, Set-in-place, Shine, Standardize, Sustain and Safety).
Originally Published InMaheshwari, S. K., & Ray, P. (2017). Texica Limited (A): A Day in the Life of a Consultant. RM0239(A). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business consultants -- Case studies; Industrial safety -- Case studies